Evaluation of the new blood-pool CT contrast agent VivoVist in mouse models - Eric W. Livingston; Jonathan E. Frank; Spencer V. Thompson; Gregory K. Wilkerson; Jean-Felix Presler; Hong Yuan (PLoS ONE, 2025)
Small animal CT imaging provides high resolution imaging of bone structure, lungs, and gross anatomy. However, it is limited in its ability to provide high soft tissue contrast. Several blood pool CT contrast agents have been developed to enhance vascular and tissue contrast for preclinical imaging with varying enhancement capabilities. VivoVist TM is the most recent commercially available blood pool CT contrast agent for preclinical applications. This study independently evaluated its radiopacity and tissue enhancement compared to two existing preclinical CT contrast agents, Mvivo-Au, and Fenestra-HDVC. Healthy nude mice were administered one of the three contrast agents. CT imaging was performed before and at 5 minutes, 1 hour, 4 hours, 24 hours, 48 hours, 96 hours, and 7 days post-injection. Tissue intensity and the enhancement ratio relative to pre-injection levels were quantified for each contrast agent at each time point. VivoVist demonstrated significantly higher blood enhancement compared to Mvivo-Au and Fenestra-HDVC at 5 minutes and 1 hour post-injection. However, the enhancement at 4 hours and later time points was inferior to that of Mvivo-Au. VivoVist exhibited the fastest blood clearance among the three contrast agents, with a blood half-life of 3.1 hours and was largely cleared from the blood by 24 hours post-injection. In CT imaging after 24 hours post-injection, VivoVist showed the highest liver enhancement, which remained high over the 7-day imaging period. Biodistribution assessment showed that the splenic uptake of VivoVist was extremely high. Histological examination of the tissues identified abundant contrast agent accumulation in the liver and spleen. No overt pathological changes were observed in either organ one month after the injection of VivoVist. Overall, the evaluation confirmed that VivoVist is an effective CT contrast agent for vascular and liver imaging with low toxicity. However, its relatively short blood half-life limits its use as a vascular contrast agent for a prolonged period.